Evaluasi Pengendalian Intern Penjualan Kredit dalam Meningkatkan Kolektibilitas Piutang pada PT Austindo Nusantara Jaya Finance - Djanegara, H. Moermahadi Soerja; Ivonie, Livia (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2006)
The collectibility of credit is influenced by the internal control of credit selling. If the internal control of credit selling has been believable and plain, then in managing its credit, the firm will be made easier because there is no negative impact from dibitors with stuck claim. When credit can be recovered in due time without any obstacle, then the collectibility degree will be high. On the contrary, when the firm does not have believable and plain internal control, it will produce negative impact on credit management because of stuck claim with the result that the collectibility degree will decrease. Keywords: Internal Control; Credit Selling; The collectibility of credit.